2020
DOI: 10.3390/brainsci10120964
|View full text |Cite
|
Sign up to set email alerts
|

Indian Medicinal Herbs and Formulations for Alzheimer’s Disease, from Traditional Knowledge to Scientific Assessment

Abstract: Cognitive impairment, associated with ageing, stress, hypertension and various neurodegenerative disorders including Parkinson’s disease and epilepsy, is a major health issue. The present review focuses on Alzheimer’s disease (AD), since it is the most important cause of cognitive impairment. It is characterized by progressive memory loss, language deficits, depression, agitation, mood disturbances and psychosis. Although the hallmarks of AD are cholinergic dysfunction, β-amyloid plaques and neurofibrillary ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 205 publications
0
25
0
Order By: Relevance
“…This medicinal plant is used to strengthen the brain, heal skin issues, and promote liver and kidney health. Gk is considered a rejuvenating herb for nerve and brain cells as it is believed to promote intelligence and improve memory [ 54 , 55 , 56 , 57 ]. In vitro studies using various Gk plant derivatives (asiaticosides, asiatic acid, madecassoside, and madasiatic acid) showed that these compounds were capable of blocking H 2 O 2 -induced cell death, decreasing free radical concentration, and inhibiting β-amyloid cell death, suggesting a potential role for Gk in the treatment and prevention of Alzheimer’s disease [ 55 , 58 , 121 , 122 ].…”
Section: Introductionmentioning
confidence: 99%
“…This medicinal plant is used to strengthen the brain, heal skin issues, and promote liver and kidney health. Gk is considered a rejuvenating herb for nerve and brain cells as it is believed to promote intelligence and improve memory [ 54 , 55 , 56 , 57 ]. In vitro studies using various Gk plant derivatives (asiaticosides, asiatic acid, madecassoside, and madasiatic acid) showed that these compounds were capable of blocking H 2 O 2 -induced cell death, decreasing free radical concentration, and inhibiting β-amyloid cell death, suggesting a potential role for Gk in the treatment and prevention of Alzheimer’s disease [ 55 , 58 , 121 , 122 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have reported the traditional use of Bacopa monnieri (L.) Pennell, Celastrus paniculatus Willd., Centella asiatica (L.) Urban, Clitoria ternatea L., Convolvulus pluricaulis Choisy, Curcuma longa L., Desmodium gangeticum (L.) DC., Evolvulus alsinoides L., Ginkgo biloba L.,Glycyrrhiza glabra L., Melissa officinalis L., Moringa oleifera Lam., Salvia officinalis L., Tinospora cordifolia (Thunb)Miers, Withania somnifera (L.) Dunal etc. in Alzheimer's disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have reported the traditional use of Bacopa monnieri, Celastrus paniculatus, Centella asiatica, Clitoria ternatea, Convolvulus pluricaulis, Curcuma longa, Desmodium gangeticum, Evolvulus alsinoides, Ginkgo biloba, Glycyrrhiza glabra, Melissa officinalis, Moringa oleifera, Salvia officinalis, Tinospora cordifolia, Withania somnifera etc. in Alzheimer's disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%